Optimasi Asupan Makanan Harian Ibu Hamil Penderita Hipertensi Menggunakan Algoritme Genetika - Novirra Dwi Asri; Imam Cholissodin; Dian Eka Ratnawati (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Hypertension is a risky disease and one of the main causes of death in pregnant women. For Hypertension pregnant women, the wrong food arrangement can affect the growth and development of the fetus. The recommended food arrangements for pregnant women with Hypertension is arrange the portion of food that can increase hypertension but not reducing the nutrition for fetus. There is one way that can be used to serve food of pregnant women with Hypertension is use a Genetic Algorithm. Genetic Algorithm is a heuristic method that uses rules to get the best solution. The process of Genetic Algorithm in research using representation chromosome integer number, crossover using extended intermediate crossover, mutation using random mutation and selection using elitism selection. The results provided are food recommendations for several days consisting of breakfast, lunch, and dinner. Based on the research results, the optimal generation size is 240 with the average fitness value is 525.0720, the optimal population size is 90 with the average fitness value is 525.0680 and the combination of cr and mr is 0.6 and 0.5 with average fitness value is 525. 0695.